An Overview of Activated Carbon Coconut Shell and Banana Trunk Fiber as Bio-Filter for Kitchen Wastewater Treatment - Nasaruddin, Nurul Syakila; Radin Mohamed, Radin Maya Saphira (Journal of Advancement in Environmental Solution and Resource Recovery, 2021)
Kitchen wastewater from the cafeteria is the presence of the chemical oxygen demand (COD), total suspended solid (TSS) and organic substances in the runoff that required rapid action. The aim of this research is to determine the concentration of COD and TSS from kitchen wastewater and to measure the influence of coconut shell activated carbon and banana trunk fiber in optimization the percentage of kitchen wastewater with tap water and time using RSM. ACCS is an activated carbon using agricultural waste which is coconut shell that act as an adsorbent to reduce pollutant. Banana trunk fiber is a bio-waste that is available in abundance to be used as bio filtration. The use of ACCS and banana trunk fiber can potentially reduce the environmental impact due to improper practice of disposal. ACCS and banana trunk fiber material have been proven by previous studies on the effectiveness to reduce the pollutant. The effectiveness of ACCS and banana trunk fiber is measured by it removal efficiency. This review has discovered that ACCS and banana trunk fiber is capable to reduce the COD and TSS concentration from KWW based on the previous studies.